KERENTANAN AIRTANAH DI DAERAH KECAMATAN GODEAN, KABUPATEN SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - SUPRAYITNO, ABDI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Godean District, Sleman Regency, Yogyakarta Special Region, is one of develop districts. An increasing number of people can not be avoided anymore, so the water needs will continue to grow. So they need a medium to regulate and protect groundwater in terms of both quality and quantity. This study aims to provide information on groundwater conditions in terms of quality with Groundwater Pollution Vulnerability Map and the terms of quantity with Groundwater Pumping Vulnerability Map. Then combine the two maps into Groundwater Pollution and Pumping Vulnerability Map. Data are collected as primary data and secondary data. Primary data are taken from depth of groundwater data and type of materials data in unsaturated zone. And secondary data from boreholes in Godean district and surrounding area, and climate data. Those datas are evaluated by Vulnerability Simple Vertical method (SVV) and Foster method to obtain two types of maps, Groundwater Pollution Vulnerability map and Groundwater Pumping Vulnerability Map. Evaluation results show Groundwater Pollution Vulnerability in Godean area has 2 vulnerability zones, high groundwater vulnerability and very high groundwater vulnerability. Groundwater Pumping Vulnerability Map in Godean District produce a groundwater vulnerability zone. Combination of two kind vulnerabilities is Groundwater Pollution and Pumping Vulnerability Map. Groundwater Pollution and Pumping Vulnerability Map in Godean District, generates two vulnerability zones, quite high groundwater vulnerability and high groundwater vulnerability. Contaminants from surface in quite high groundwater vulnerability can reach groundwater within several months to 3 years and the groundwater surface can have drawdown easily. And contaminants in high vulnerability area can enter groundwater within several days to a year and the groundwater surface can have drawdown very easily. These map can be used for groundwater protection in the Godean District both quality and quantity